NURSE EXPERIENCE IN CONDUCTING TRIAGE AT THE EMERGENCY INSTALLATION OF SANTA ELISABETH SAMBAS GENERAL HOSPITAL - Rupina, Sumarni; Ngadiran, Antonius; Hotmaida, Linda (Institut Kesehatan Immanuel, 2023)
Introduction. The Emergency Department is a healthcare unit that caters to emergency situations. In the emergency service department of a hospital, one crucial process is Triage. Before receiving any medical treatment, patients who arrive suddenly at the Emergency Department must undergo Triage, so that they can receive appropriate care based on the urgency of their condition. Objective. To explore the meaning of nurses' experiences in implementing Triage in the Emergency Department at Santa Elisabeth Hospital, Sambas. Method. This research adopts a Qualitative research design with a Phenomenological study approach. The sample consists of 6 nurses who work in the Emergency Department of Santa Elisabeth Hospital, Sambas. Results. The findings reveal that the implementation of Triage is a complex and vital aspect of healthcare service. Conclusion. The research concludes that the implementation of Triage is a complex and crucial aspect of healthcare service in the Emergency Department of Santa Elisabeth Hospital, Sambas, West Kalimantan.